Impact of inflammatory bowel disease on perioperative complications in patients undergoing surgery for metastatic spinal tumors - Le Fan; Kenan Sun; Wanshan Shang; Zifeng Wang; Jiayi Guo; Lanbo Yang (Frontiers in Medicine, 2026)
Background The global prevalence of inflammatory bowel disease (IBD) continues to rise. However, researchers have not yet investigated how IBD influences perioperative complication rates in patients undergoing surgical intervention for metastatic spinal tumors. This study used the United States National Inpatient Sample (NIS) to evaluate the association between IBD and perioperative complications in patients undergoing surgery for metastatic spinal tumors. Methods Patients undergoing surgical treatment for spine metastases from 2016 to 2022 were identified through ICD-10-CM diagnostic coding, and their data were analyzed. The study population excluded individuals younger than 18 years. Participants were stratified according to whether they had IBD or not, and comparisons were made across demographic characteristics, hospital-related factors, intraoperative parameters, comorbid conditions, and perioperative complications. The statistical methodology encompassed Pearson χ 2 analysis, Wilcoxon rank-sum testing, and logistic regression modeling. The perioperative complications were selected based on their clinical relevance, availability within the NIS database, and consistency with previous nationwide database studies evaluating postoperative outcomes following spine surgery. Results Among 48,465 patients with metastatic spinal tumors 535 (1.1%) had concurrent IBD. Patients with IBD exhibited significantly higher odds of developing various perioperative complications. These included wound disruption (aOR = 5.41; P < 0.001), post-procedural hematoma (aOR = 4.57; P = 0.002), post-procedural infection (aOR = 3.83; P < 0.001), gastrointestinal system complications (aOR = 3.36; P < 0.001), and cerebrospinal fluid leakage (aOR = 1.93; P = 0.014). Conclusions Patients with IBD undergoing surgery for metastatic spinal tumors were at significantly increased risk of wound-related complications, post-procedural hematoma, postoperative infection, gastrointestinal complications, and cerebrospinal fluid leakage. These findings support careful preoperative risk stratification and individualized perioperative management in this high-risk population.